STRATEGIC TALENT MANAGEMENT IN THE DIGITAL AGE: LEVERAGING INTELLIGENT SYSTEMS FOR WORKFORCE EFFICIENCY - Sridar, S. Preetham (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In an era defined by rapid digital transformation, organizations are under increasing pressure to adapt their human capital strategies to meet evolving business demands and technological shifts. Traditional approaches to talent management, once sufficient for linear, static environments, are now proving inadequate in the face of continuous disruption, skills obsolescence, and increasing workforce complexity. This research paper examines the strategic reorientation of talent management by integrating intelligent systems, including artificial intelligence (AI), machine learning (ML), and people analytics, to achieve greater workforce efficiency, agility, and alignment with long-term organizational objectives. The study examines how data-driven, intelligent systems are reshaping core HR functions ranging from recruitment and onboarding to performance management, learning, and succession planning. Drawing from both empirical data and contemporary organizational case studies, this research underscores the shift from reactive human resource management to proactive talent optimization. Intelligent systems enable the identification of high-potential candidates, prediction of employee attrition, customization of development pathways, and dynamic workforce planning — all of which are essential for navigating a volatile labor market. A critical aspect of this study is the evaluation of how strategic talent management must transcend mere automation. It must foster a symbiotic relationship between technology and human decision-making, where analytics guide actions but do not overshadow ethical judgment and cultural considerations. As organizations deploy AI in talent decisions, ethical governance frameworks, transparency, and employee trust emerge as critical success factors. The findings suggest that organizations that strategically embed intelligent systems into their talent ecosystem experience measurable improvements in operational efficiency, employee engagement, and talent retention. Moreover, these systems offer a competitive edge by enhancing the organization’s ability to respond rapidly to skill gaps, emerging roles, and global workforce shifts. This paper concludes that intelligent systems are not merely tools but strategic enablers of next-generation talent management. Their value lies not in replacing human capability but in augmenting it, making talent strategies more precise, inclusive, and aligned with organizational vision. In doing so, businesses position themselves to not only survive but thrive in the digital age, where the ability to harness human capital through strategic intelligence will define future success